2004
DOI: 10.1097/01.asn.0000129981.50357.1c
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure after Nonmyeloablative Hematopoietic Cell Transplantation

Abstract: Abstract. Acute renal failure (ARF) is a common life-threatening complication after myeloablative allogeneic hematopoietic cell transplantation (HCT). Nonmyeloablative HCT aims to eradicate the malignancy with graft-versus-tumor effect, rather than with high doses of chemoradiotherapy. It may be anticipated that a lower risk of ARF exists in nonmyeloablative HCT as a result of the milder preconditioning regimen. However, the patients who receive the nonmyeloablative HCT are older individuals who are not eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 29 publications
(30 reference statements)
4
79
3
Order By: Relevance
“…22 In this study, the mortality rate of patients within 1 year was found to be 27.4%, which was lower than that reported earlier. 5,8 Therefore, we suggested that nonmyeloablative HSCT might be a safe therapy for younger patients and for elderly patients without baseline organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In this study, the mortality rate of patients within 1 year was found to be 27.4%, which was lower than that reported earlier. 5,8 Therefore, we suggested that nonmyeloablative HSCT might be a safe therapy for younger patients and for elderly patients without baseline organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may act solely or collectively to cause renal failure. 7,8 aGVHD may affect the kidney through cytokine-and immune-related injury, including glomerular deposits, leading to nephrotic syndrome and tubulitis. 21 However, other studies showed that dehydration because of diarrhea in patients with aGVHD II-IV is most likely to be the cause of AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70,74,77,78 Mortality rates are often elevated in the most severe form of TA-TMA, 72 whereas milder cases present an increased risk for CKD. 66 As in the general population, diabetes mellitus, 32 previous hypertension, 26 previous renal impairment, 79 sepsis, 13 amphotericin use, 80 requirement for mechanical ventilation 33 and admission to the intensive care unit 26 were all associated with increased risk for AKI following HCT. In actual fact, pre-HCT comorbidities greatly impact the outcome of patients undergoing HCT.…”
Section: Pathogenesismentioning
confidence: 99%
“…The major culprit for AKI in nonmyeloablative HCT is calcineurin inhibitors injury by themselves or in association with other etiologies, namely sepsis, nephrotoxicity or GVHD. 12,32,33 In both myeloablative allogeneic and nonmyeloablative HCT, calcineurin inhibitors are employed as prophylaxis against GVHD. One of the most common and serious complications associated with calcineurin inhibitors is their nephrotoxicity, manifested as AKI (mostly reversible after dose reduction) or as progressive CKD (usually irreversible).…”
Section: Pathogenesismentioning
confidence: 99%